2008
DOI: 10.1371/journal.pone.0004030
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Relationships between Hepcidin, Anemia, Infections and Inflammatory Cytokines in Pediatric Refugees: A Cross-Sectional Study

Abstract: BackgroundHepcidin, a key regulator of iron homeostasis, is increased in response to inflammation and some infections, but the in vivo role of hepcidin, particularly in children with iron deficiency anemia (IDA) is unclear. We investigated the relationships between hepcidin, cytokines and iron status in a pediatric population with a high prevalence of both anemia and co-morbid infections.Methodology/Principal FindingsAfrican refugee children <16 years were consecutively recruited at the initial post-resettleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
71
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 54 publications
17
71
2
4
Order By: Relevance
“…While this paper was under revision, a study on anemia in pediatric refugees was published that found an association of decreased urinary hepcidin levels with hemoglobin, ferritin, and serum iron but not to IL-6 concentrations. 42 This is in accordance with our observed lack of differences in circulating IL-6 levels between ACD (high serum hepcidin) and ACD/IDA subjects (low serum hepcidin), suggesting that the erythroid demand for iron is a more powerful regulator of hepcidin expression than inflammation-induced hepcidin formation. However, as a limitation of this study, we were not able to distinguish between the effects of a putative erythropoietic stimulation and the effects of iron deficiency on hepcidin expression when analyzing the combined effects of bleeding and inflammation, although EPO levels were significantly higher in ACD/IDA compared with ACD subjects.…”
Section: Discussionsupporting
confidence: 91%
“…While this paper was under revision, a study on anemia in pediatric refugees was published that found an association of decreased urinary hepcidin levels with hemoglobin, ferritin, and serum iron but not to IL-6 concentrations. 42 This is in accordance with our observed lack of differences in circulating IL-6 levels between ACD (high serum hepcidin) and ACD/IDA subjects (low serum hepcidin), suggesting that the erythroid demand for iron is a more powerful regulator of hepcidin expression than inflammation-induced hepcidin formation. However, as a limitation of this study, we were not able to distinguish between the effects of a putative erythropoietic stimulation and the effects of iron deficiency on hepcidin expression when analyzing the combined effects of bleeding and inflammation, although EPO levels were significantly higher in ACD/IDA compared with ACD subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we were not able to examine WBC, CRP, and PCT levels due to inadequate blood volume collected from the healthy children. The levels of the biomarkers at the time the samples were taken may not reflect their actual levels because our data are cross-sectional, the half-lives of sepsis markers are different (14,(25)(26)(27), and the majority of patients had received antibiotic and fluid therapy prior to the PICU. Hepcidin is severely affected by anemia parameters such as serum and storage iron levels of patients regardless of the level of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It takes place in oxygen transport, protein synthesis, and function of enzymes. Adequate iron stores are necessary for normal childhood growth and development [1,2]. Although the biological importance of iron has been known since ancient times, there have been new developments in the field of absorption and storage of the iron during the the last decade, especially in the last 2-3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroportin exports iron into plasma from duodenocytes, hepatocytes and erythrophagocytosing macrophages [5]. Measurement of hepcidin concentrations in serum or urine is thought to be useful to differentiate iron-deficiency anemia from anemia of infection [2]. Ferroportin is the sole known iron exporter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation